Sequência didática sobre lançamento de foguetes utilizando garrafas pet para estudantes de formação de docentes - (:unkn) unknown (Universidade Estadual de Ponta Grossa (UEPG), 2025)
Building and launching rockets from PET bottles, whether returnable or not, are excellent resources for Physics classes, regardless of grade level. Furthermore, it demonstrates the wealth of knowledge that can be explored through their use in the classroom, especially regarding the interdisciplinarity between Physics and Chemistry. Thus, this dissertation aims to teach Physics content—such as vectors, quantities, and vector decomposition; oblique launch with and without air resistance; drag force and terminal velocity; center of mass, center of gravity, and center of pressure; hydrostatic pressure and hydrodynamic pressure; variable mass systems; the equation of state for an ideal gas—as well as Chemistry content, including chemical reactions and balancing chemical equations. Teaching these content involved diverse strategies, such as contextualized theoretical classes, practical experimental activities, building PET bottle rockets for launch, and the use of software and computer simulators. To implement and facilitate the presentation of this content, a teaching notebook was developed for students and teachers, with suggestions on how to apply it. Initially, this material was designed for use in Elementary School (EFAF) and High School (EM) classes. However, it was actually implemented in a second-year class of the Teacher Training Course (FD), integrated with high school, at Colégio Sagrada Família, located in Ponta Grossa, Paraná. The teaching intervention took place in the afternoon between October and November 2024, during which time the proposed methodology, based on David Ausubel's theory of meaningful learning and Lev Vygotsky's socio- interactionist theory, was implemented. To assess student performance, mind maps were used as an assessment tool, administered at two different times: the first and last class. This approach aimed to compare student progress before and after the teacher's intervention, using the teaching notebook. IRAMUTEQ software was used to quantitatively and qualitatively analyze the mind maps constructed by students before and after the application of the textbook during class, using word clouds and similarity graphs generated by the software. This work was not completed in 2024 and will continue until May 2025. The results obtained in 2025 are presented in Appendix F.
Keywords: Ensino de Física; Foguetes de Garrafa PET; Formação de Docentes; Química; Vygotsky; Ausubel